PENENTUAN SOLID CONTENT PADA PRODUK DISPERSI - Imelda Bahar (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
Dispersion products are widely used in various industries, especially the paint industry. Paint is defined as a liquid that is used to coat the surface of a material with the aim of beautifying, strengthening, or protecting the material. So that the paint produced can be produced properly, then several tests on the dispersing material are carried out including solid content analysis. Solid content is a characteristic that was first carried out to determine the polymer content contained in the finished product. Gravimetric method where the measurement is directly with one tool namely CEM Smart Turbo Moisture / Solid Analizer so that the measurement of solid content is faster compared to using an oven. The results of the average measurement of solid content in sample A were obtained from CEM Smart Turbo Moisture / Solid Analizer 48.05 % and oven 48.35 %, in sample B from CEM Smart Turbo Moisture / Solid Analizer 99.55 % and oven 99, 75 %, and in the C CEM sample Smart Turbo Moisture / Solid Analizer 55.71% and oven 55.94 %. Solid content measurement results obtained from CEM Smart Turbo Moisture / Solid Analizer and oven are still within the limits set by a company.